A tecnologia criativa do soundpainting: contexto, reflexões e expansões - João Paulo Prazeres de Oliveira Campos (2022)
This work aims to critically examine the creative process carried out through soundpainting, a system of collective and collaborative artistic creation based on gestural signs which is continuously developed since the 1970s by American artist Walter Thompson and is, currently, disseminated and practiced globally. For this purpose, we contextualize the soundpainting processes, establishing connection points with musical practices of the 20th and the 21st centuries and weaving critical reflections related to the development of soundpainting artistic practices. Based on the author's experience with soundpainting, examples of strategies are described and critically commented in order to discuss possible ways of developing creative processes in dialogue with soundpainting.